Teacher’s Mental Health in Students Perspective and Its Contribution to Student’s Achievement of Islamic Religious Studies - Nurbaiti, Nurbaiti (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe purpose of this study is to determine teacher’s mental health according to student’s perspective and its contribution to student’s achievement in Islamic Religious Studies. The study was conducted at Azhari Elementary School of Jakarta and involved 52 students as research participants, with a stratified simple random sampling. This research used test and questionnaire as instruments to collect data. The data validity by correlation coefficient of point biserial (r pbi) and correlation coefficient of product moment (r xy). The data reliability by KR 21 and alpha cronbach (a). The results proved, the teacher’s mental health contributed 54 % to student’s achievement of Islamic religious studies. AbstrakTujuan dari penelitian ini adalah untuk mengetahui tentang kontribusi kesehatan mental guru dalam perspektif siswa terhadap prestasi belajar Pendidikan Agama Islam. Penelitian ini dilakukan di SD Azhari Cilandak Jakarta dengan menggunakan sampel sebanyak 52 siswa. Teknik pengambilan sample dengan stratified simple random sampling. Instrument yang digunakan adalah tes dan angket. Validitas data yang digunakan adalah koefisien korelasi point biserial (rpbi) dan koefisien korelasi produk momen (rxy). Reliabilitas data dilakukan dengan menggunakan KR 21 and alpha cronbach (a). Hasil penelitian menunjukkan bahwa kesehatan mental guru memberikan kontribusi sebesar 54 persen terhadap prestasi belajar siswa.